A Case of Diagnosed Systemic Lupus Erythematous With Antenatal Complications (International Journal of Scientific Research and Management (IJSRM), 2016)
This is a case report of SLE complicating pregnancy. During antenatal period preeclampsia was managed LSCS wasdone for IUGR with abnormal doppler. Patient discharged in stable condition and followed. Patient was continued onoral hydroxychloroquine and prednisolone throughout pregnancy and postpartum period.